Antioxidant Activity and Functional Properties of Polymerized Whey Products by Glycation Process - Liliana Ortega; Anabel Romero; Claudia Muro; Francisco Riera (International Journal of Polymer Science)
The antioxidant properties of sweet and acid whey products were incremented by polymerization of their proteins by glycation of whey protein concentrates (WPC) and their hydrolyzates (WPCH) with ribose and glucose in individual experiments under similar concentration. Heating at 50°C during 20 h maximum and pH 7 and pH 9 were used in all tests. The higher activity was found in WPC glycosylates products with ribose at pH 7 and heating during 10–15 h. In comparable form, antioxidant activity in WPCH was incremented by prior hydrolysis to glycation with 25–45% of hydrolysis degree. Further functional properties of whey proteins (solubility, emulsion, and foam) were also improved by the polymerization with ribose. The color of polymerized products due to Maillard reactions was associated with antioxidant activity of each compound; however comparative color in glycosylates products with glucose and ribose did not show this effect.